Mapping deprivation in Mozambique: An analysis of census data (1997-2007) - José Cardoso; Jo\~ao Morgado; Vincenzo Salvucci (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
In this study we analyse the evolution of deprivation indicators and of a multidimensional poverty index using Mozambican census data for 1997 and 2007. We analyse deprivation levels according to eight different indicators reflecting housing conditions and access to public utilities/basic services. Using the Alkire Foster method, we also construct a multidimensional poverty index based on the selected deprivation indicators. The results are presented at the provincial and administrative post levels. They suggest that more than two-thirds of households could be considered poor in 2007 with respect to the chosen deprivation dimensions. We also identify marked geographical disparities in the incidence of poverty and deprivation both among and within provinces.
Keywords: I31; O18; R15; 330; multidimensional poverty; deprivation; Mozambique